Pelatihan Penggunaan Aplikasi Mendeley untuk Sitasi Artikel Ilmiah pada Jurnal Bereputasi Nasional - Wilyanti, Liza Septa; Wulandari, Sovia; Asfahani, Asfahani; Priyanto, Priyanto (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
This article contains the results of training on using the Mendeley application conducted by Jambi University lecturers and students. This training needs to be carried out to help teachers master the use of the Mendeley application to cite scientific articles in nationally reputable journals. This paper aims to improve the writing of scientific articles for teachers at SMP Negeri 7 Muaro Jambi. The method used in the implementation of this service is participatory story action research (PAR). The participants in this training were teachers at SMP Negeri 7 Muaro Jambi. From the results of the implementation of activities, teachers can understand well about 1) basic material related to plagiarism; 2) material for using the Mendeley application; and 3) skilled at using the Mendeley application for citation of scientific articles in nationally reputable journals. The conclusion of this activity is that it has a positive impact in the form of mastering the use of Mendeley application citations to improve scientific article writing among teachers of SMP Negeri 7 Muaro Jambi.